General practitioners' perceptions of public reporting of institution and individual medicine prescribing data - Xin Du; Xinping Zhang; Yuqing Tang (BMC, 2016)
Abstract Background Public reporting of institution- and individual-level performance data has recently become a popular topic in the health care field. This study (1) evaluated the perceptions of general practitioners on the public reporting of institutional and individual medicine prescribing data in primary care institutions, and (2) compared the difference among the perceptions of general practitioners on the dimensions of necessity, methodological rigor, and impact of public reporting medicine prescribing data. Methods We conducted a survey in 10 primary care institutions in Q city, Hubei province. General practitioners who hold prescribing license were eligible for this study; we surveyed all eligible general practitioners in July 2014. The survey instrument was developed based on previous studies and expert opinions. Paired t-test or nonparametric test was used to evaluate the difference in perceptions between the institutional and individual medicine prescribing data reporting. An analysis of variance test was used to analyze the score differences among the three dimensions (i.e., necessity, methodological rigor, and impact). Results A total of 154 general practitioners were surveyed in this study. No significant difference in the perceptions of general practitioners was observed between the institution- and individual-level medicine prescribing data reporting (p > 0.05). General practitioners have significantly different perceptions on the three dimensions of the institution- and individual-level data reporting (p < 0.05). Methodological rigor obtained the lowest score. Regarding the strategies to facilitate the medicine prescribing data reporting, over 80 % of general practitioners selected the items that disclose process measures and not outcome measures, as well as educate patients on data interpretation. Conclusion The perceptions of general practitioners between institution- and individual-level data reporting have no significant difference. General practitioners place their utmost concern on public reporting on the methodological rigor. Processing measures and patient education to improve the efficiency of public reporting require substantial attention.